2008
DOI: 10.1002/ddr.20229
|View full text |Cite
|
Sign up to set email alerts
|

LBY135, a novel anti‐DR5 agonistic antibody induces tumor cell–specific cytotoxic activity in human colon tumor cell lines and xenografts

Abstract: TRAIL (TNF-related apoptosis-inducing ligand) induces apoptosis on binding to DR4 and DR5 receptors on the surface of tumor cells. These receptors are of particular interest in the development of cancer therapeutics as they preferentially mediate tumor cell apoptosis. We have generated a chimeric anti-DR5 agonistic antibody, LBY135, from its murine parental antibody, LCR211, identified using hybridoma technology. Both LCR211 and LBY135 specifically bind to DR5 with nanomolar affinity, mimic TRAIL to induce cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…However, IgG molecules are bivalent, and as shown in this study, higher valencies and nonantibody molecular formats can lead to vastly superior activation of TRAILR2-mediated apoptosis. This explains why some agonistic antibodies against TRAILR2 show low or no in vitro activity in the absence of higher-order cross-linking and are less active than soluble TRAIL trimer (7,38,39). Despite the fact that such antibodies have lower valency, they can exhibit antitumor activity in murine xenograft studies (7,8,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IgG molecules are bivalent, and as shown in this study, higher valencies and nonantibody molecular formats can lead to vastly superior activation of TRAILR2-mediated apoptosis. This explains why some agonistic antibodies against TRAILR2 show low or no in vitro activity in the absence of higher-order cross-linking and are less active than soluble TRAIL trimer (7,38,39). Despite the fact that such antibodies have lower valency, they can exhibit antitumor activity in murine xenograft studies (7,8,39).…”
Section: Discussionmentioning
confidence: 99%
“…This explains why some agonistic antibodies against TRAILR2 show low or no in vitro activity in the absence of higher-order cross-linking and are less active than soluble TRAIL trimer (7,38,39). Despite the fact that such antibodies have lower valency, they can exhibit antitumor activity in murine xenograft studies (7,8,39). A recent study with drozitumab, an agonistic TRAILR2 mAb, showed that binding to Fcg receptors was essential to the antitumor activity in mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…dose of M413 (based on internal pilot studies) or 6 hrs after the last of three 200 μg i.p. doses of LCR211 administered as previously described [30]. …”
Section: Methodsmentioning
confidence: 99%
“…Since the in-vivo anti-tumor activity of LBY135 has been verified in human colorectal xenograft models in mice [94], Novartis is recruiting patients for an open-label, multi-center, twoarm Phase I/II trial of LBY135 alone and in combination with capecitabine in advanced solid tumors (Nevada Cancer Institute, Las Vegas, NV, USA) [95]. Leukemia [101] TRAIL-R1 HDAC inhibitors Enables transcription by blocking gene acetylation Leukemia [102] TRAIL-R2 HDAC inhibitors Histone deacetylase inihbition Malignant tumor cells [103] TRAIL-R2 Proteasome inhibitors Inhibits protein degradation Prostate [104], colon [105], lung [106] TRAIL-R2 Radiotherapy Induction of DNA damage Prostate [106], leukemia [107], breast, lung, colon [108] TRAIL-R2 NSAIDs Inhibition of COX-1 and 2 Colon [109], lung [110], prostate and colon [111] TRAIL-R1 and TRAIL-R2 Proteasome inhibitors Inhibits protein degradation Leukemia [112] TRAIL-R1 and TRAIL-R2 HDAC inhibitors Enables transcription by blocking gene deacetylation…”
Section: Clinical Application Of Trail-r Mabsmentioning
confidence: 99%